Multifunctional Mesoporous Polydopamine With Hydrophobic Paclitaxel For Photoacoustic Imaging-Guided Chemo-Photothermal Synergistic Therapy - Zhang, Liren (Int J Nanomedicine, 2019)
BACKGROUND: Chemo-photothermal therapy has attracted intensive attention because of its low side effects and better therapeutic efficiency. Although many photothermal agents have been loaded with chemotherapeutic drugs for chemo-photothermal therapy, their applications are limited by complex synthetic protocols and long-term safety. Therefore, there is significant clinical value in the development of a simple system of biocompatible and biodegradable photothermal nanomaterials with high payloads of chemotherapeutic drugs for chemo-photothermal synergistic therapy. MATERIALS AND METHODS: In this study, PEG-modified polydopamine nanoparticles with mesoporous structure (MPDA-PEG) were successfully obtained by an emulsion-induced interface assembly strategy. Subsequently, paclitaxel (PTX) dissolved in acetone was loaded into the mesoporous channels of MPDA-PEG nanoparticles by solution absorption method. A PTX-loaded MPDA-PEG (MPDA-PEG-PTX) nanoplatform for combination of photothermal therapy (PTT) and chemotherapy was developed. RESULTS: The synthesized MPDA-PEG nanoparticles had a great photothermal effect under near-infrared (NIR) laser irradiation and exhibited an enhanced photothermal effect with the increase of particle size. Meanwhile, MPDA-PEG nanoparticles also had a high payload of PTX, and the PTX release could be greatly accelerated by elevated temperature from photothermal effect. In MTT cytotoxicity assay, A549 cells incubated with MPDA-PEG-PTX under NIR laser irradiation (PTT + chemotherapy group) exhibited better therapeutic effect than single chemotherapy (MPDA-PEG-PTX group) and PTT (MPDA-PEG + Laser group). The synergistic therapeutic effect of MPDA-PEG-PTX with NIR laser irradiation in vivo was further investigated under the guidance of photoacoustic imaging (PAI), tumors of nude mice treated with MPDA-PEG-PTX with NIR laser irradiation were completely eliminated with minimal side effect. CONCLUSION: The MPDA-PEG-PTX nanoplatform is a simple and effective platform which can completely inhibit tumor growth with minimal side effects under NIR irradiation, and it exhibits better therapeutic effect than single chemotherapy and PTT.